The effect of job stress on vocational adjustment at Sirte university - E. M. Elgobbi, F. A. Mohammed (Journal of Pure & Applied Sciences, 2018)
The aim of this study is to indicate the effect between the level of job stress and the level of vocational adjustment among the teaching staff members at Sirte university. The descriptive approach was used to examine the phenomenon and analyze the data of study variables in order to reach the desired results. The study population consisted of the teaching staff members in all faculties of Sirte university. The study sample consisted of about (167) teaching staff members. The questionnaire was used as a tool for the study, it included three sections: personal information (5) items, work stress (12) items, functional compatibility (12) items. The researchers used the SPSS program to analyze the responses of the teaching staff members. Some statistical methods such as means, standard deviations, and other statistical methods were used to achieve the required results. This study found that there was a statistically significant effect between the averages of the sample regarding the levels of job stress according to job satisfaction. The study also found a statistically significant effect between the averages of the sample with regard to the levels of job stress according to the satisfactoriness. Among the most important recommendations of this study is that the need to pay attention to teaching staff members and meet their requirements and create a spirit of cooperation among them, in order to achieve the public interest of the university. The study also recommends the need to increase the salaries and financial benefits to the teaching staff members in order to serve the basic objectives of the university.